Формування і функціонування ринків продукції галузі птахівництва в Україні - Григор’єв, Сергій Олегович (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня кандидата економічних наук зі спеціальності 08.00.03 «Економіка та управління національним господарством». Національний університет біоресурсів і природокористування України. Київ, 2018. У дисертації уточнено зміст понять «ринок» та «аграрний ринок». Розкрито основні функції аграрного ринку на основі позицій провідних вітчизняних та зарубіжних науковців. У межах дослідження систематизовано інструменти державного регулювання аграрного сектору та виділені ті з них, що по-перше, направлені на збалансування попиту і пропозиції на аграрному ринку держави, та, по-друге, – на підвищення ефективності сільськогосподарського виробництва. Проаналізовано основні економічні показники функціонування ринку продукції галузі птахівництва в Україні та за кордоном. Здійснено оцінку рівня конкурентоспроможності вітчизняної продукції птахівництва та проведено комплексний аналіз перспектив у торгівлі для України на ринках країн-членів ЄС, уникаючи демпінгування. На основі індексів порівняльних переваг здійснено прогноз індексів конкурентоспроможності по категорії м’ясо курей до 2021 року. Обґрунтовано стратегічні напрями забезпечення продовольчої безпеки України шляхом національного виробництва продукції галузі птахівництва з метою забезпечення стабілізаційної функції держави. Запропоновано шляхи зменшення імпортозалежності галузі птахівництва України за наявним продуктивним поголів’ям птиці
Thesis for the degree of candidate of economic sciences, specialty 08.00.03 Economics and Management of National Economy. National University of Life and Environmental Sciences of Ukraine. Kyiv, 2018. This dissertation is focused on enhancement of theoretical and methodical justification and working out the practical recommendations to improve the functioning of poultry products markets in Ukraine. The theoretical basis of market relationships and main functions of agricultural market defined. It has been determined, that the fundamental element of the agricultural market system is the effective demand of the population. The most important factor of agricultural policy is pricing. In the dissertation, the author clarifies the concepts of «market» and «agricultural market». The main functions of the agricultural market are disclosed on the basis of the positions of leading domestic and foreign scientists. Within the framework of the study, the instruments of state regulation of the agrarian sector are systematized and divided into two groups: first – aimed at balancing supply and demand in the agrarian market of the country, and second – increasing the efficiency of agricultural production. The main economic indicators of the functioning of the poultry industry in Ukraine and abroad are analyzed. The assessment of the level of competitiveness of domestic poultry products has been made and a comprehensive analysis of the prospects for Ukraine’s trade in the EU markets has been carried out in order to avoid dumping. Based on the indexes of comparative advantages, the forecast for the categories of «chicken meat» and «egg powder» until 2021 has been made. It was determined that main specificities of agricultural market are: limited scope of market laws, part of the products created in agriculture becomes the resource for following processing, the freedom of the agricultural producer is limited to climate conditions and seasonality, lack of high qualified specialists, forming and development of private farming, inelastic demand for agricultural products. The instruments of governmental regulation of agricultural sector have been systematized and divided into instruments for effectiveness enhancement of agricultural production and instruments to provide social protection of rural population and development of infrastructure of agricultural territories. The main theories of market equilibrium have been researched and it is determined that the moving power of genesis or economy theories is the change of conditions of the economical processes (change of the consumption and production structure, strengthening of globalization, development of information technologies, etc.), however none of the researched conceptions (A. Marshall, L. Walras, V. Pareto) can be considered as universal. It was determined that the following system of methodological principles of complex analysis of agricultural market shall be used: dedication, complexity, consistency, objectivity, dynamism, efficiency and taking into consideration the territorial specificities. The main factors were defined that form the market situation on world food markets and affect the local food market, such as: war conflict and migration between countries and continents, increase of imports of food products, growth of the population, increase of imports of food products to the developing countries that cannot fully supply themselves of own production food; growth of the competition between similar food products of the producers from different countries; pricing policies of different countries and different methods of stimulation of the development of food production (subsidy of local production); changes of exchange rates of locals currencies to US dollar; climate conditions; natural disasters that can lead to huge demand for food on the market; changes in tastes and requirements of the customers of the world food market. It’s been proven that poultry is the most perspective among other types of meat, as it has the most competitive pricing. Most of the countries are first of all, focused on providing the population with the protein of adequate quality, structure and origin. The nutrition experience shows that animal proteins are very useful for human’s health and increase in life expectancy. Local producers often manufacture competitive products in noncompetitive ways that characterized by high energy and materials use, increased labor input, low wages and profits. It is demonstrated that the food security strategy has to be directed to provide the necessary amount of food of own production and, if needed, at the expense of shortening of volatility of offer and crop production, adequate management of national food supply, development of transport infrastructure and distribution systems, providing the access of all segments of population to existing food resources. It’s justified that planned significant growth of production volumes of poultry meat is only possible when the investment climate for the industry is positive, what is described by stable, foreseeable government policy to support the local producers in budget, credit, pricing and management spheres of government management and establishing of production of high technology equipment considering the innovative technologies. It’s been proven that it’s necessary to regulate the prices for poultry products that are being exported because it affects the profits and competiveness of the exporters. Price dumping as one of the ways to gain competitive advantages for Ukrainian producers was analyzed. It’s determined that it is only practical for starting stage, as it brings the number of negative consequences that can cause loss of profit, fall of profitability or even losses in production. The imports dependency of the poultry industry of Ukraine has been proven and ways to reduce it by growing and diversification of export orientation of the goods produced by the industry were proposed
Keywords: аграрний ринок; продукція птахівництва; конкурентоспроможність; виробництво; продовольча безпека; демпінг; імпорт; експорт; імпортозалежність; agricultural market; industry; forming; poultry products